Physiological differentiation of viridans streptococci. - Facklam, R R (1977)
Twelve hundred and twenty-seven clinical isolates and eighty stock strains of viridans streptococci were tested for serological and physiological characteristics. Because the serological reactions of these strains varied, a differentiation scheme could not be based on these reactions. For the same reason, there could be no correlation of serological characteristics with physiological characteristics. Nearly 97% of the clinical isolates were speciated by differences in physiological characteristics. Ten different physiological species were recognized. The physiological speciation scheme was based on stable enzymatic reactions rather than on results of tolerance tests. The study included air-tolerant anaerobic streptococcal strains as well as viridans streptococcal strains not normally found in humans. The differentiation scheme and nomenclature of the author are related to those of other investigators. Differences in the distribution of species isolated from different clinical sources and human infections were also noted. A key for the differentiation of human isolates of viridans streptococci is proposed.